Multiomics analyses and machine learning of nuclear receptor coactivator 6 reveal its essential role in hepatocellular carcinoma. Issue 1 (7th November 2022) - Fang, Yinghao; Xu, Yuyan; Liao, Wei; Ji, Tao; Yu, Linyuan; Li, Longhai; Pan, Mingxin; Yang, Dinghua
Abstract: Nuclear receptor coactivator 6 (NCOA6), a coactivator of numerous nuclear receptors and transcription factors, regulates multiple critical cellular functions. Nuclear receptor coactivator 6 is dysregulated in various cancers, including hepatocellular carcinoma (HCC); however, its role remains largely unknown. Here we reported that NCOA6 was highly expressed in HCC compared to the adjacent liver tissue, and NCOA6 overexpression was significantly correlated with poor HCC prognosis. Experiments revealed that the knockdown of NCOA6 damaged the proliferation, migration, and invasion of HCC cells. Multiomics and immune infiltration analyses showed a close relationship between NCOA6 expression, multiple cancer‐related malignant pathways, and the immunosuppressive microenvironment. Finally, we established an effective NCOA6‐related microRNA (miRNA) signature to distinguish HCC from hepatitiscirrhosis patients. To the best of our knowledge, this study is the first to provide a comprehensive analysis of NCOA6 expression in HCC. We found that NCOA6 plays an important role in HCC development and has a potential mechanism of action. Establishing an NCOA6‐related miRNA signature will help develop novel diagnostic strategies for HCC patients. Abstract : This study comprehensively investigated the function of NCOA6 in HCC using multi‐omics analyses (including genomics, transcriptome, and proteome) based on public databases, machine learning and various experiments. We found that NCOA6 plays an important role in HCC development and has a potential mechanism of action. Moreover, we established an effective NCOA6 related microRNAs signature for HCC detection.